Silica supported copper nanoparticles prepared via surface organometallic chemistry: active catalysts for the selective hydrogenation of 2, 3-dimethylbutadiene. (19th December 2016) - Boukebbous, K.; Merle, N.; Larabi, C.; Garron, A.; Darwich, W.; Laifa, E. A.; Szeto, K.; De Mallmann, A.; Taoufik, M.
Abstract : Mesitylcopper reacts with silica to give supported clusters, then reduced to nanoparticles. These catalysts allow the selective hydrogenation of 2, 3-dimethylbutadiene to 2, 3-dimethyl-1-butene. Materials were characterized in detail. Abstract : 2, 3-Dimethylbutadiene can be highly selectively hydrogenated to 2, 3-dimethyl-1-butene with a new catalyst based on silica supported copper nanoparticles (Cu-NPs) prepared via surface organometallic chemistry. Mesityl-copper was firmly grafted onto silica and the reduction of the resulting surface species under hydrogen at 350 °C led to well-dispersed Cu-NPs. Prior to catalytic tests, the final catalysts as well as the intermediates were characterised by DRIFT, SS NMR, EPR, TEM, XRD and elemental analyses.